Life Safety and Civil Protection in Natural Emergencies - Erkinov Ilkhom Erkin Ogli (Genius Journals, 2023)
This article provides information on how to conduct rescue operations in the area of the city ruins.
Keywords: City ruins; public buildings; earthquakes; rescue operations